The “coronéis” – from Mendonça to Paulo Honório: notes about typicality and realism in S. Bernardo - Bastos, Hermenegildo (Revista do Instituto de Estudos Brasileiros, 2015)
Considering the Brazilian modernist legacy, of which he was always a critic heir, Graciliano Ramos in S. Bernardo makes his narrator-character go through the writer’s problems in the struggle to grasp the meaning of human fate, in a situation of life’s degradation and flattening. Writing reveals itself in the end as the path to comprehending the process of dehumanization. But in order to achieve that, it is necessary to go beyond the representation of the mere singularity life and route itself to the construction of the type, understood as a capable way of shedding light upon the contradictions. The theory of the type, or particularity, as elaborated by Lukács, reveals here its value and actuality.